Geochronology and geochemistry of subducted Cadomian continental basement in central Iran: Decompressional anatexis along the Jurassic Neotethys margin - Jamali Ashtiani, Rezvaneh; Hassanzadeh, Jamshid; Schmitt, Axel Karl; Sudo, Masafumi; Timmermann, Martin; Günter, Christina; Sobel, Edward (Gondwana research, 2020)
Late Neoproterozoic-Early Cambrian calc-alkaline granitoids are ubiquitous in the continental basement of Iran and indicate formation within a Cadomian arc system at the northern margin of Gondwana. A basement complex comprising mainly mica schist, paragneisses, and metagranite along with metabasite and rare pegmatite is exposed in the Zayanderud region north of Shahrekord located in the hinterland of the Zagros mountain range. This complex is unique in the Neotethyan realm because it includes eclogites with Jurassic metamorphic ages implying involvement of continental crust at the onset of subduction. Ion microprobe UPb zircon dating along with trace element and oxygen isotope analyses for metagranites define two zircon age clusters of ca. 552 and 565 Ma confirming connection with the other Ediacaran age basement arc plutons in the belt. Zircon geochronology for pegmatite, by contrast, yielded a concordant age population averaging 176.5 ± 3.3 (2σ) Ma. Zircon crystals from the pegmatite also have unusually low rare earth element (REE) abundances with sharp increases towards the heavy REE. Along with an absence of a negative Eu anomaly, this indicates a high-grade metamorphic origin of zircon crystallizing from a pegmatite which was formed by melting of mica schist and possibly amphibole eclogite during decompression where incipient garnet breakdown released Zr and HREE to form zircon, and LREE were retained in stable apatite and titanite. Corresponding 40Ar/39Ar phengite dates from the pegmatite and the mica schist country-rock are overlapping with or only slightly postdate the UPb zircon ages, indicating rapid cooling after reaching maximum metamorphic pressure in the Early Jurassic. The Zayanderud basement complex is thus potentially a rare example of deep burial of continental crust and rapid exhumation due to buoyant escape during the incipient stages of subduction, well before the ultimate closing of the Neotethys ocean basin between Arabia and Eurasia in the mid-Tertiary.